Periprosthetic fracture after cementless revision total hip arthroplasty with a tapered, fluted monobloc stem: a retrospective long-term analysis of 121 cases - Bischel, Oliver E.; Seeger, Jörn Bengt; Böhm, Paul M. (Journal of Clinical Medicine, 2025)
Background: The use of tapered monobloc stems in revision total hip arthroplasty (RTHA) has shown excellent results, with low implant-dependent failures due to aseptic loosening. Infection is one of the main failure reasons, but further problems, like periprosthetic fractures (PPFs), may endanger the function and duration of the implant in the long run. Methods: A consecutive series of 121 cases after femoral RTHA with a monobloc device was retrospectively investigated, and a Kaplan-Meier analysis was performed. The mean follow-up was 13.0 (range: 0.8-23.8) years. Results: PPF occurred in six patients during follow-up. The cumulative risk for PPF was 5.2% (95% CI: 1.1-9.4%) after 23.8 years. Female gender was associated with a significantly higher risk compared to male gender (9.1% (95% CI: 2.1-16.1%) after 23.1 years vs. 0% after 23.8 years; log-rank p = 0.0034). Patients operated with stems with a length equal to or longer than the calculated median length were also at a significantly higher risk of PPF during follow-up (10.2% (95% CI: 2.4-17.9%) after 23.8 years vs. 0% after 23.1 years; log-rank p = 0.0158). Diabetes at the time of index operation also significantly influenced the occurrence of a PPF during follow-up (n = 4 patients with PPF out of 107 without (4.0% (95% CI: 0.2-7.8%) after 23.8 years vs. n = 2 out of 14 with diabetes (15.4% (95% CI: 0-35.0%) after 21.1 years; log-rank p = 0.0368). The failure rate with implant removal as an endpoint due to aseptic loosening was 0%, and with infection it was 3.4% (95% CI: 0.1-6.7%), after 23.8 years. Conclusions: Although no removal of the implant due to a PPF was necessary, the cumulative risk for PPF after femoral revision with a tapered and fluted monobloc stem was higher in this long-term follow-up series compared to implant failure due to infection or aseptic loosening. Female gender and diabetes was associated with a significantly higher risk of PPF during follow-up. The use of longer stems than necessary is not preventive of PPF, and should be avoided.
Gesehen am 29.09.2025